Genome-Wide Discovery of Genes Required for Capsule Production by Uropathogenic Escherichia coli - Kelvin G. K. Goh; Minh-Duy Phan; Brian M. Forde; Teik Min Chong; Wai-Fong Yin; Kok-Gan Chan; Glen C. Ulett; Matthew J. Sweet; Scott A. Beatson; Mark A. Schembri (mBio, 2017)
ABSTRACT Uropathogenic Escherichia coli (UPEC) is a major cause of urinary tract and bloodstream infections and possesses an array of virulence factors for colonization, survival, and persistence. One such factor is the polysaccharide K capsule. Among the different K capsule types, the K1 serotype is strongly associated with UPEC infection. In this study, we completely sequenced the K1 UPEC urosepsis strain PA45B and employed a novel combination of a lytic K1 capsule-specific phage, saturated Tn5 transposon mutagenesis, and high-throughput transposon-directed insertion site sequencing (TraDIS) to identify the complement of genes required for capsule production. Our analysis identified known genes involved in capsule biosynthesis, as well as two additional regulatory genes (mprA and lrhA) that we characterized at the molecular level. Mutation of mprA resulted in protection against K1 phage-mediated killing, a phenotype restored by complementation. We also identified a significantly increased unidirectional Tn5 insertion frequency upstream of the lrhA gene and showed that strong expression of LrhA induced by a constitutive Pcl promoter led to loss of capsule production. Further analysis revealed loss of MprA or overexpression of LrhA affected the transcription of capsule biosynthesis genes in PA45B and increased sensitivity to killing in whole blood. Similar phenotypes were also observed in UPEC strains UTI89 (K1) and CFT073 (K2), demonstrating that the effects were neither strain nor capsule type specific. Overall, this study defined the genome of a UPEC urosepsis isolate and identified and characterized two new regulatory factors that affect UPEC capsule production. IMPORTANCE Urinary tract infections (UTIs) are among the most common bacterial infections in humans and are primarily caused by uropathogenic Escherichia coli (UPEC). Many UPEC strains express a polysaccharide K capsule that provides protection against host innate immune factors and contributes to survival and persistence during infection. The K1 serotype is one example of a polysaccharide capsule type and is strongly associated with UPEC strains that cause UTIs, bloodstream infections, and meningitis. The number of UTIs caused by antibiotic-resistant UPEC is steadily increasing, highlighting the need to better understand factors (e.g., the capsule) that contribute to UPEC pathogenesis. This study describes the original and novel application of lytic capsule-specific phage killing, saturated Tn5 transposon mutagenesis, and high-throughput transposon-directed insertion site sequencing to define the entire complement of genes required for capsule production in UPEC. Our comprehensive approach uncovered new genes involved in the regulation of this key virulence determinant.